2016
DOI: 10.1093/ntr/ntw157
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized Crossover Trial of Electronic Cigarette Sampling Among Smokers

Abstract: Introduction: Electronic cigarette (EC) use is proliferating, but initial uptake patterns and their influence on smoking remains unclear. This study of EC sampling examines naturalistic uptake of ECs, as well as effects on smoking and perceived reward from smoking and vaping. Methods: Within a double-blind randomized crossover design, smokers (n = 24; 75% male; M age = 48.5 years) smoked as usual for 1 week, followed by two counterbalanced naturalistic (ie, ad libitum use) weeks of either placebo or active fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In fact there is reason to suggest that outcomes would be even stronger (vs. control conditions) for newer and more powerful ENDS devices, if only because they are generally more efficient in nicotine delivery, offer improved battery duration, and wider flavor assortment (45,47), all of which presumably increase consumer appeal and eventual uptake. Third, our comparison group herein was a non-sampling control, as opposed to a placebo e-cigarette condition, studied elsewhere (49). We were less interested in the nicotine-specific effects of e-cigarette uptake and more interested on the aggregate experience of trying a new product vs. not.…”
Section: Discussionmentioning
confidence: 99%
“…In fact there is reason to suggest that outcomes would be even stronger (vs. control conditions) for newer and more powerful ENDS devices, if only because they are generally more efficient in nicotine delivery, offer improved battery duration, and wider flavor assortment (45,47), all of which presumably increase consumer appeal and eventual uptake. Third, our comparison group herein was a non-sampling control, as opposed to a placebo e-cigarette condition, studied elsewhere (49). We were less interested in the nicotine-specific effects of e-cigarette uptake and more interested on the aggregate experience of trying a new product vs. not.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies investigated smokers not motivated to quit. They found that the addition of free e‐cigarettes to usual care (information and motivational text messages) did not increase sustained smoking abstinence; 35 provision of free e‐cigarettes for use entirely at the discretion of participants did not significantly influence quit attempts or biologically verified abstinence; 36 and randomization to ad libitum nicotine‐containing rather than non‐nicotine‐containing e‐cigarettes did not reduce regular cigarette use 37 …”
Section: Effects On Smoking Cessationmentioning
confidence: 99%
“…12 This variability is reflected in switching studies, which show that some, but not all, smokers have successfully switched from tobacco cigarettes to e-cigarettes, compensating for nicotine via a new nicotine-delivering product. 10,[13][14][15][16][17][18][19] To date, several studies indicate that e-cigarettes do not expose users to carbon monoxide [13][14][15][16][17][18][20][21][22][23] ; however, evidence regarding other tobacco smoke constituents is limited. Comparative analyses indicate that exposure to polycyclic aromatic hydrocarbons (PAHs) was significantly lower among exclusive vapers compared to smokers.…”
Section: Introductionmentioning
confidence: 99%